Use of Trauma‐Informed Care With Incarcerated Offenders. Issue 1 (6th April 2020) - Pringer, Sarah M.; Wagner, Nathaniel J.
Abstract : Regardless of preexisting trauma history, offenders regularly experience traumatic events while incarcerated. Current therapeutic approaches focus on coping skills and behavioral responses. The authors recommend integrating the use of trauma‐informed care to address the deeper emotional responses tied to trauma.